Dental caries prevalence and caries-associated risk factors of students aged 12–15 in Xide County of Liangshan Prefecture, China: a cross-sectional study - Yong Yang; Suzhen Sun; Yiting Lou; Xiaoyan Weng; Chenghui Xie; Haiying Ma; Zheyuan Sun; Qianting Wang; Kaile Ji; Binbin Ying (BMJ Open)
Objective About 2 billion people have caries in permanent teeth, and 514 million children have caries in primary teeth worldwide. Regional disparities in caries prevalence are evident in various areas of China. A comprehensive understanding of the status of dental caries and its associated risk factors is essential for developing effective dental health policies in economically disadvantaged regions. Thus, this study aims to examine the prevalence of dental caries and its risk factors among students aged 12–15 in Xide County, a remote mountainous area in China.Design In this cross-sectional study, dental health surveys were conducted using self-administered questionnaires and the Decayed-Missing-Filled Tooth (DMFT) Index. An oral clinical examination was carried out by the criteria and guidelines set forth by WHO.Setting Xide County, Liangshan prefecture, China in 2022.Participants 558 students aged 12–15 years completed the survey.Results The study conducted in Xide County found a dental caries prevalence of 42.5% among 12–15 year-old students, with a mean DMFT of 1.50 (SD=2.25). Multivariable logistic regression analysis identified several significant risk factors for dental caries (p<0.05), including starting brushing after the age of six (OR 0.34, 95% CI 0.17 to 0.65), brushing teeth less than once a day (OR 9.24, 95% CI 5.53 to 15.33) and consuming carbonated drinks more than once a day (OR 0.28, 95% CI 0.14 to 0.53). Additionally, the use of fluoride (OR 0.61, 95% CI 0.43 to 0.85) and awareness of its protective effect on teeth (OR 0.75, 95% CI 0.59 to 0.98) were found to be associated with a lower risk of dental caries (p<0.05).Conclusion The prevalence of dental caries among students aged 12–15 in Xide County was identified as a significant public oral health concern. The oral health behaviours of students were found to be influenced by factors at the family and community levels.